Games based learning in mathematics education: A systematic literature review - Dika Faiz Himmawan; Dadang Juandi (Universitas Sarjanawiyata Tamansiswa, 2023)
This study aims to describe and evaluate the effects of game-based mathematics learning. Systematic Literature Review (SLR) is used as a method in this research by collecting primary studies through checking the Google Scholar database, Education Resources Information Center (ERIC) from 2013 to 2022 with the keywords